To solve the factored quadratic equation \((19x - 3)(9 + x) = 0\), we can find the values of \(x\) by setting each factor equal to zero.
-
Set the first factor equal to zero: \[ 19x - 3 = 0 \] Solving for \(x\): \[ 19x = 3 \quad \Rightarrow \quad x = \frac{3}{19} \]
-
Set the second factor equal to zero: \[ 9 + x = 0 \] Solving for \(x\): \[ x = -9 \]
Now we have two solutions: \(x = \frac{3}{19}\) and \(x = -9\).
To present the solution set with the lesser number first: \[ { -9, \frac{3}{19} } \]
So, the solution set is \({-9, \frac{3}{19}}\).